A theoretical framework for strengthening occupational safety and health and 5S as a foundation for industrial culture - Sujastika, Ismi; Endarto, Danil; Fauzan, Ahmad (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2026)
Despite the rapid expansion of Industry 4.0, a significant gap persists between vocational graduates' technical skills and the professional character required by industry, particularly regarding safety culture and discipline. This study aims to develop an integrative theoretical framework that positions Pancasila Education as a foundational value system to strengthen Occupational Safety and Health (K3) and 5S practices in fostering holistic work readiness. This research employs a conceptual literature review with a thematic synthesis approach, analysing peer-reviewed national and international literature published between 2019 and 2025. The synthesis reveals that work readiness is a multidimensional construct where technical competence must be balanced with "industrial citizenship"—a workplace civic character characterised by ethical responsibility and safety-oriented behaviour. The findings suggest that Pancasila values provide the normative basis, K3 acts as the manifestation of respect for human dignity, and 5S serves as the habituation mechanism. Integrating these three elements transforms K3 and 5S from mere technical procedures into pedagogical tools for professional character formation. This study offers a novel interdisciplinary perspective by integrating civic education, safety culture, and vocational pedagogy to produce ethically grounded, industry-ready graduates.